A fast sensor for in vivo quantification of cytosolic phosphate in Saccharomyces cerevisiae - Zhang, Jinrui; Sassen, Tom; Ten Pierick, Angela; Ras, Cor; Heijnen, Joseph J.; Wahl, Sebastian Aljoscha (Biotechnology and Bioengineering, 2015)
Eukaryotic metabolism consists of a complex network of enzymatic reactions and transport processes which are distributed over different subcellular compartments. Currently, available metabolite measurement protocols allow to measure metabolite whole cell amounts which hinder progress to describe the in vivo dynamics in different compartments, which are driven by compartment specific concentrations. Phosphate (Pi) is an essential component for: (1) the metabolic balance of upper and lower glycolytic flux; (2) Together with ATP and ADP determines the phosphorylation energy. Especially, the cytosolic Pi has a critical role in disregulation of glycolysis in tps1 knockout. Here we developed a method that enables us to monitor the cytosolic Pi concentration in S. cerevisiae using an equilibrium sensor reaction: maltose+Pi <=> glucose+glucose-1-phosphate. The required enzyme, maltose phosphorylase from L. sanfranciscensis was overexpressed in S. cerevisiae. With this reaction in place, the cytosolic Pi concentration was obtained from intracellular glucose, G1P and maltose concentrations. The cytosolic Pi concentration was determined in batch and chemostat (D=0.1 h-1) conditions, which was 17.88μmol/gDW and 25.02μmol/gDW, respectively under Pi-excess conditions. Under Pi-limited steady state (D=0.1 h-1) conditions, the cytosolic Pi concentration dropped to only 17.7% of the cytosolic Pi in Pi-excess condition (4.42μmol/gDW vs. 25.02μmol/gDW). In response to a Pi pulse, the cytosolic Pi increased very rapidly, together with the concentration of sugar phosphates. Main sources of the rapid Pi increase are vacuolar Pi (and not the polyPi), as well as Pi uptake from the extracellular space. The temporal increase of cytosolic Pi increases the driving force of GAPDH reaction of the lower glycolytic reactions. The novel cytosol specific Pi concentration measurements provide new insight into the thermodynamic driving force for ATP hydrolysis, GAPDH reaction, and Pi transport over the plasma and vacuolar membranes.
CRIS-Team Scopus Importer:2022-01-11
Keywords: Compartmentation; Cytosolic Pi; In vivo; Metabolomics; Quantitative metabolomics; S. cerevisiae